Urban micro climate performance in deferent urban fabric in Mosul, Iraq - Hassan Ali, D. Turki (2008)
City of Mosul has a traditional urban core called old city, side by side with a modern fabric adopted by municipal authority since the rapid urbanization which the city had witnessed in the fifties of the last century, the traditional one characterizes with a compact and organic tissue, Introverted courtyard buildings built with a heavy thick masonry structure, while the modern is open geometric one with a wide streets and extraverted buildings build with concrete. City of Mosul has a hot dry climate summers and cool rainy winter, this research aims to make a comparative study for the urban micro climate performance (air temperature and relative humidity) in the two deferent urban fabrics (traditional and modern), during both the hottest and the coldest period of the year, using the meteorological data as a reference for evaluating the performance. The way cities are planned and built is therefore important for the global energy use environmental comfort. So it’s important to study the relationship between urban form and outdoor climate. The preliminary results confirm that the climatic conditions are much more stable in the traditional city than in the modern part of the city, regarding both air temperature and relative humidity.